PEDAGOGICAL CONDITIONS OF FORMATION OF ECOLOGICAL CULTURE IN CHILDREN OF PRIMARY SCHOOL AGE - L.P. Lysohor (Academy of Cognitive and Natural Sciences, 2010)
In the article the role of the cognitive-experienced activity is examined during forming of ecological concepts. It was certain that during supervisions junior schoolboys cognize the natural phenomena and processes independently, by the analysis of changes which take place in an environment.